Peran Dewan Pendidikan dalam Meningkatkan Mutu Pelayanan Pendidikan - Hendarman -- (Jurnal Pendidikan dan Kebudayaan, 2012)
Board of education has been established the issuance of Minister of National Education decree number 044/U/2002 concerning Board of Education and School Committee and the Government Gazette number 17 year 2010 concerning the implementation and management of education. In principle, this board plays the role as society representatives in improving quality improvement, equality and efficiency of educational management. Also, this board could play as the mediator for the needs and aspiration of society related to educational policies taken by local government and schools. This study focused on the analysis of 2 (two) main research questions, namely to what extent the stakeholders are aware of this board and its roles, and the barriers that this board encounters in its implementation. The findings showed that this board has yet to 1) be the strategic partner of the local government and schools, 2) maximally function in a number of districts/cities, and 3) contribute for the education advancement. It is recommended that the establishment of this board shall be based on the principles of transparent, accountable, and democratic. In addition, it is suggested to encourage the regular meetings between local education authorities and board of education aims for the analysis of critical issues in the local areas for its solutions. ABSTRAK Keberadaan Dewan Pendidikan masih dipertanyakan terkait dengan peningkatan mutu pelayanan pendidikan. Meskipun sudah dibentuk di berbagai provinsi/kabupaten/kota, tampaknya dewan ini masih belum dianggap sebagai mitra bagi berbagai pemangku kepentingan khususnya pemerintah daerah dalam rangka peningkatan mutu pelayanan pendidikan. Penelitian ini mengkaji berbagai kegiatan atau terobosan yang telah dilakukan Dewan Pendidikan khususnya dalam kaitan peningkatan mutu pelayanan pendidikan serta kendala-kendala yang dihadapi untuk melaksanakan peran tersebut. Data dan informasi diperoleh dari data primer dan sekunder yang berasal dari hasil wawancara dan analisis informasi terkait yang dimunculkan dalam berbagai media termasuk surat kabar dan situs-situs. Secara umum, dewan pendidikan telah berpartisipasi dan memberikan kontribusi dalam upaya meningkatkan mutu pelayanan pendidikan dengan merujuk kepada standar nasional pendidikan. Kendala-kendala yang dihadapi dewan pendidikan lebih sebagai akibat belum adanya persepsi dan apresiasi yang sama dari pemerintah daerah terhadap keberadaan dan peran dari dewan pendidikan.